Polyphenols and minerals in propolis from different agricultural regions of Uruguay - Pablo Cracco; Maria Cristina Cabrera; Giovanni Gallieta; Ali Saadoun (Agrociencia Uruguay, 2024)
The broad spectrum of plant origin of propolis makes them very heterogeneous in terms of their chemical composition. This fact conditions the potential use in medicine. Among the main bioactive components, polyphenols and minerals are related to different medicinal properties attributed to propolis. This study aims to identify and quantify the presence of 15 polyphenols and 8 minerals, in a collection of georeferenced propolis from 14 locations in Uruguay. Polyphenols in ethanolic extracts of propolis were identified and quantified by HPLC, while minerals were studied by atomic absorption spectroscopy in crude propolis. The plant environment was characterized using information on the productive use of the soil. The three main polyphenols found in all locations were chrysin, galangin and pinocembrin. All polyphenols analyzed were found, except rutin, which was not detected in any sample. Regarding the concentration of polyphenols, we can divide Uruguay into two regions: the southwest with high concentrations of 125 g/kg, and the northeast with concentrations of 16 g/kg. All minerals were identified. The variations between localities and seasons rule out the use of minerals for a determination of geographical origin. The description of the plant environment was partially adjusted with the types of propolis. Concentrations found of polyphenols and minerals are within the values reported in the world. Studies on the high polyphenolic content of propolis from the southwestern region should continue due to its potential medicinal use.